SKILL MANAGEMENT TRAINING IN IMPROVING ADOLESCENT PRODUCTIVITY DURING THE COVID-19 PANDEMIC IN LONTAR VILLAGE - Yuary Farradia; Mora Mora; Indra Kusumawati; Wahyu Widodo; Mamay Komarudin (Yayasan Education and Social Center, 2021)
This devotion involves many components of society to become organizational boosters, as teachers and volunteers. The community wants to realize non-formal education that can embrace the lower middle class who do not get access to formal education for various reasons or children break up. school because of the narrowness of the economy. The goals and objectives to be achieved in this Community Service (PKM) activity are to guide adolescent citizens learning to increase their productivity in the pandemic period. Covid-19 by developing business ideas that match their talents/potential and by the opportunities and needs of the community. The method used in community service (PKM) activities is to provide counseling and discussion in providing training and direction to the youth of citizens. Learn to increase its productivity in the current Covid-19 pandemic online with the Zoom application. With the impact of the Covid-19 pandemic that is widespread and unavoidable, there needs to be an increase in the ability of citizens to learn to increase their productivity by developing ideas and capturing business opportunities in the community that are tailored to their potential. With this pelatihan, it is expected that wara learn to have the ability to be able to develop ideas and capture business opportunities amid the Covid-19 pandemic. In increasing the productivity of the villagers, learning the village is needed not only for brilliant ideas and wide open opportunities but also for business planning. Well structured